Vegetation structure, zonation, and seedling establishment in the Asajaya Mangove Forest, Sarawak, Malaysia - Khairul Adha, Bin A. Rahim. (Universiti Malaysia Sarawak (UNIMAS), 2000)
Research was conducted to examine physical and biological factors which affect the establishment and forest structure of mangrove community and to understand the patterns of past and present mangrove distribution.